Age Demographics as a Moderating Effect in the Influence of Fintech Through Financial Literacy on Financial Behavior - Ibnu Andaris; Niken Paramitha; Dadan Firmansyah; Muhamad Ekhsan (Petra International Journal of Business Studies, 2024)
The increasingly sophisticated development of technology gave rise to the term fintech in the financial aspect; the emergence of fintech brought challenges for users that affect financial behavior. This study seeks to analyze in more depth what factors can influence financial behavior using fintech variables, financial literacy, and age demographics. The leading theory presented is planned behavior, which is related to financial behavior. This research uses a quantitative approach by collecting primary data through observation and distributing questionnaires. Based on our study, a sample size of 100 individuals was selected by purposive sampling technique. The analysis employed path analysis with moderating effects, conducted through Smart-PLS 3 software. The results revealed a statistically significant influence of financial technology and financial literacy on financial behavior. Furthermore, financial technology exhibited a significant impact on financial literacy. Additionally, we found that financial literacy was a mediator in the relationship between financial technology and financial behavior, while age demographics did not moderate this association.